Investasi Asing Langsung dan Pertumbuhan Ekonomi di Negara OKI: Peran Moderasi Stabilitas Politik - Muhammad Nurwahyudi; Wendy; Anggraini Syahputri; Anwar Azazi; Uray Ndaru Mustika (PT. PENERBIT TIGA MUTIARA, 2025)
Economic growth is a key indicator in assessing a country's ability to sustainably increase the output of goods and services. This study aims to analyze the effect of trade openness (TO) and the interaction between foreign direct investment (FDI) and political stability (PS) on economic growth in member countries of the Organization of Islamic Cooperation (OIC). The study utilizes panel data from 30 OIC member countries over the period 2005–2023, sourced from the World Bank’s World Development Indicators (WDI). The analytical method employed is panel data regression using the Fixed Effect Model (FEM) to control for individual heterogeneity across countries, as well as Moderated Regression Analysis (MRA) to test the moderating role of PS in the relationship between FDI and economic growth. The estimation results show that both TO and FDI have a positive and significant impact on economic growth. However, the interaction between FDI and PS exhibits a negative and significant effect, which contradicts conventional theoretical expectations that political stability should enhance the positive impact of FDI. These findings suggest that in several OIC countries, despite relatively low political stability, FDI continues to flow in response to economic opportunities, strategic interests, or domestic market appeal. In other words, political instability does not always serve as a major barrier to foreign investment, especially when the economic potential remains high. Moreover, FDI under such conditions may serve as an important instrument to strengthen international economic cooperation, expand production capacity, and drive long-term economic growth. These findings provide strategic implications for the formulation of investment and institutional stability policies in OIC countries.